The Decline of Amylase Level of Pancreatic Juice After Pancreaticoduodenectomy Predicts Postoperative Pancreatic Fistula. Issue 10 (November 2016) - Furukawa, Kenei; Gocho, Takeshi; Shirai, Yoshihiro; Iwase, Ryota; Haruki, Koichiro; Fujiwara, Yuki; Shiba, Hiroaki; Misawa, Takeyuki; Yanaga, Katsuhiko
Abstract : Objectives: Postoperative pancreatic fistula (POPF) is a life-threatening complication after pancreaticoduodenectomy (PD). The aim of this study is to evaluate the significance of pancreatic amylase level of pancreatic juice for PF after PD. Methods: The subjects were 46 patients who underwent PD between January 2012 and August 2015 at Jikei University Hospital. We retrospectively investigated the relation between patient characteristics including pancreatic amylase level of pancreatic juice through the pancreatic drainage tube and the incidence of POPF (grade B or grade C according to the International Study Group on the Pancreatic Fistula) using univariate and multivariate analyses. The decline of pancreatic amylase level of pancreatic juice was evaluated by 1 − postoperative day 3/postoperative day 1 ratio. Results: In univariate analysis, nonductal adenocarcinoma ( P = 0.0252), soft pancreatic remnant ( P = 0.0155), and decline of pancreatic amylase level of pancreatic juice ≥ 80% ( P = 0.0010) were significant predictors of POPF. In multivariate analysis, decline of pancreatic amylase level of pancreatic juice of 80% or greater ( P = 0.0192) was the only significant independent parameter. Conclusions: Decline of pancreatic amylase level of pancreatic juice can predict POPF after PD. Abstract : Supplemental digital content is available in the text.